Terrorism - Martin, Claudia (Our world in crisis, 2018)
What is terrorism? How do terrorists differ from other criminals? What makes some individuals and groups decide to use violence to create terror as a means of achieving their aims? This book looks at the history of terrorism and analyses the motivations for its use. It looks at what is being done to tackle terrorism and asks readers to think about what they can do to help people in countries affected by terrorism, for example by fundraising for organisations supporting victims of terrorist attacks